Self-sustaining library services through strategic fee-based initiatives: a roadmap for academic library administrators in Nigeria - Olaseigbe, Yetunde Faith; Ozonuwe, Opene Sunday; Ogunojemite, Abosede Tola; Rotimi, Racheal Ajibola; Giwa, Ayokunle Oluwadamilola; Ogundana, Ayomide Ayoola (Communicate: Journal of Library and Information Science, 2025)
This study investigates the potentials of fee-based library services as a self-sustaining model for academic libraries in Nigeria, addressing funding challenges and enhancing service delivery. A review of existing literature and empirical findings reveals that strategic fee-based initiatives can generate revenue, promote innovation, and improve user satisfaction. The study identifies ten fee-based services, including digitization, research assistance, citation management, digital literacy training, virtual reference services, interlibrary loan services, study space reservations, technology lending, digital media conversion, and data management and curation. However, challenges such as poor planning, user resistance, and inadequate marketing hinder the effectiveness of fee-based services. To overcome these challenges, the study recommends market research, user education, targeted marketing, service quality improvement, accountability, and user feedback mechanisms. By implementing these strategies, academic libraries in Nigeria can develop self-sustaining fee-based services, diversify revenue streams, and enhance their contributions to academic success and national development. This study provides a roadmap for library administrators to navigate the transition to fee-based services, ensuring the long-term sustainability of academic libraries in Nigeria.